2016
DOI: 10.1097/qai.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Perturbs the IL-7 Axis, Promoting Senescence and Exhaustion that Broadly Characterize Immune Failure in Treated HIV Infection

Abstract: Background HIV-infected patients who fail to normalize CD4 T cells despite suppressive antiretroviral therapy have impaired immune homeostasis: diminished naïve T cell numbers, elevated T cell turnover, senescence and inflammation. Methods Blood samples from immune failures (n=60), immune successes (n=20) and healthy controls (n=20) were examined for plasma IL-7 levels, for cellular expression of the IL-7Rα chain (CD127), for the exhaustion and senescence markers PD-1 and CD57, and for the survival factor Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 58 publications
4
57
0
2
Order By: Relevance
“…Consistent with previous observations [18], we found that CD127 expression was diminished in T cells from IF subjects and other studies indicate that IL-7 is increased in plasma of IF subjects [26]. It is possible, therefore, that reduced CD127 expression is a consequence of increased chronic exposure of T cells to high concentrations of IL-7 in vivo leading to IL-7 hyporesponsiveness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous observations [18], we found that CD127 expression was diminished in T cells from IF subjects and other studies indicate that IL-7 is increased in plasma of IF subjects [26]. It is possible, therefore, that reduced CD127 expression is a consequence of increased chronic exposure of T cells to high concentrations of IL-7 in vivo leading to IL-7 hyporesponsiveness.…”
Section: Discussionsupporting
confidence: 92%
“…IL-7 induced Akt phosphorylation (P-Akt) is linked to cell cycle progression and T cell proliferation [15, 16]. Plasma IL-7 levels in IF patients are increased when compared to IL-7 levels in patients who recovered CD4 T cells [17]. In contrast, the capacity of CD4 T cells to respond to IL-7 stimulation as measured by rapid induction of P-STAT5 is diminished in IF patients and associated with reduced expression of CD127 [18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, they found positive associations between baseline CD127 density on CD4 + T cells and an increase in CD4 + RTE cell counts and naïve CD4 + T‐cell counts after 2 years of effective ART, indicating that CD127 expression on CD4 + T cells is a predictor of increased thymic output after 2 years of suppressive ART . Furthermore, a few studies have found that in INRs, plasma levels of IL‐7 were elevated and CD127 expression both on CD4 + and CD8 + T cells was decreased; however, there was no statistically significant correlation between the baseline plasma IL‐7 level and absolute CD4 + T‐cell count after successful ART . Furthermore, others have shown a positive association or a negative association between baseline plasma IL‐7 levels and CD4 recovery in HIV‐1‐infected individuals after ART initiation.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 93%
“…In the absence of ART, increased expression of PD-1 was associated with accelerated decline in CD4 + T cells following acute infection 48 and untreated chronic infection 36 . Following ART, PD-1 expression on CD8 + T cells has been associated with impaired CD4 + T cell immune reconstitution 49 microvascular disease 50 , elevated oxidised high and low density lipoproteins 51 and a shorter time to viral rebound once ART was stopped 52 .…”
Section: Introductionmentioning
confidence: 99%